Levels of Cytokines and MicroRNAs in Individuals With Asymptomatic Hyperuricemia and Ultrasonographic Findings of Gout: A Bench‐to‐Bedside Approach - Estevez‐Garcia, Irving O.; Gallegos‐Nava, Selma; Vera‐Pérez, Erika; Silveira, Luis H.; Ventura‐Ríos, Lucio; Vancini, Gonzalo; Hernández‐Díaz, Cristina; Sánchez‐Muñoz, Fausto; Ballinas‐Verdugo, Martha A.; Gutierrez, Marwin; Pineda, Carlos; Rodriguez‐Henriquez, Pedro; et al. (Arthritis care & research (2010), 2018)
Objective To assess potential associations among serum cytokines and microRNA (miR) levels with ultrasound (US) findings suggestive of urate deposits in chronic asymptomatic hyperuricemia and gout. Methods All participants underwent musculoskeletal US and measurements of serum interleukin‐1β (IL‐1β), IL‐2, IL‐4, IL‐5, IL‐6, IL‐8, IL‐10, IL‐12, IL‐13, interferon‐γ, tumor necrosis factor, monocyte chemoattractant protein 1, and epithelial neutrophil–activating peptide 78, as well as miR‐146a, miR‐155, and miR‐223 levels. Results Thirty individuals with asymptomatic hyperuricemia, 31 normouricemic controls, and 30 patients with gout were included. The frequency of synovitis and double contour sign using US was similar between asymptomatic hyperuricemia (67% and 27%, respectively) and patients with gout (77% and 27%, respectively), and each had a higher frequency than controls (45% and 0%, respectively). Serum IL‐6 and IL‐8 levels were similar between patients with asymptomatic hyperuricemia (mean ± SD 69.7 ± 73.4 and 18.5 ± 25.6 pg/ml, respectively) and gout (mean ± SD 75.8 ± 47.6 and 24.4 ± 31.7 pg/ml, respectively), and higher than controls (mean ± SD 28.2 ± 17.6 and 7.4 ± 6.0 pg/ml, respectively). A similar distribution was observed for miR‐155 levels in asymptomatic hyperuricemia, patients with gout, and controls (mean ± SD 0.22 ± 0.18, 0.20 ± 0.14, and 0.08 ± 0.04, respectively). Associations between morphostructural abnormalities suggestive of urate deposits (regardless of clinical diagnosis) and serum markers were assessed. Subjects with urate deposits had higher IL‐6 (257.2 versus 47.0 pg/ml; P = 0.005), IL‐8 (73.2 versus 12.0 pg/ml; P = 0.026), and miR‐155 (0.21 versus 0.16; P = 0.015) levels than those without deposition findings. Conclusion In individuals with chronic asymptomatic hyperuricemia, the presence of synovitis and double contour sign by US may represent a subclinical manifestation of monosodium urate crystal nucleation, capable of triggering inflammatory pathways (IL‐6 and IL‐8) and mechanisms of intercellular communication (miR‐155), similar to what is observed in patients with gout.